The Challenges of Gender Equality and Women's Rights in Yemen: A Sociological Survey - Al-Mansoob, Mohammed; Nugroho, Rino Ardhian; Kartono, Drajat Tri; Al-Aghbari, Areeg Gameel (Wawasan: Jurnal Ilmiah Agama dan Sosial Budaya, 2024)
The study explores the complicated issues of women's rights and gender equality in Yemen, a nation whose deeply ingrained cultural norms and patriarchal standards limit women's participation in public life and sustain economic inequality. It seeks to advance the conversation on gender equality worldwide by offering a comprehensive analysis of the Yemeni environment and suggesting future directions for development. Using a mixed-methods approach that includes a theoretical analysis, a literature study, and an across-sectional sociological survey, the research examines gender systems locally and globally. It evaluates Yemen's women's rights situation. Results reveal a generational gap in knowledge of gender rights, with younger respondents being more informed than older generations, who were more influenced by conventional standards. Gender discrimination endures despite advancements in healthcare and education, with issues of pay inequality and violence against women being significant concerns. The report highlights the main obstacles to gender equality as patriarchal attitudes, economic inequalities, difficulties in education and the workplace, and widespread violence against women. The goal of improving women's political representation ends by promoting the creation of a Gender Equality Commission, encouraging female entrepreneurship, questioning patriarchal conventions, and putting affirmative action laws into place. It emphasises the importance of continual research and observation to evaluate how well these policies promote social justice in Yemen.